Parámetros fisicoquímicos y efecto del aceite esencial de hojas de origanum vulgare sobre íleon aislado de cavia porcellus” - Carranza Barreto, Karen Estephanie (2016)
This research aimed to determine the physico-chemical parameters and evaluate the effect of essential oil of Origanum vulgare leaves on isolated ileum Cavia porcellus. the essential oil obtained by distillation method entrainment of water vapor, yielding 1,14%. refractive index, density and pH were determined, obtaining average values of 1,4772, 0,9107 and 5,20 respectively. The oil was soluble in ethanol 96 °G.L., dichloromethane and chloroform. The organoleptic characteristics were: aromatic odor, camphor; light yellow; bitter, slightly spicy, astringent flavor and oily texture. The antispasmodic effect was determined by testing on guinea pig isolated ileum, using PowerLab equipment, for which he worked with 7 specimens. The results of the pharmacological evaluation showed that the essential oil concentrations of 0,5%, 1%, 2,5% and 4% generated effect on motility respect to amplitude and frequency of contractions induced by acetylcholine and histamine in isolated ileum Cavia porcellus; showing no statistically significant difference between the concentrations (p > 0,05). The oil esecial 4% (0,2 mLdose) showed a greater similarity to the clinical effect of N-butyl bromide hyoscine and chlorpheniramine